Phase 1 trial of carfilzomib (PR-171) in combination with vorinostat (SAHA) in patients with relapsed or refractory B-cell lymphomas. Issue 3 (3rd March 2016) - Holkova, Beata; Kmieciak, Maciej; Bose, Prithviraj; Yazbeck, Victor Y.; Barr, Paul M.; Tombes, Mary Beth; Shrader, Ellen; Weir-Wiggins, Caryn; Rollins, April D.; Cebula, Erin M.; Pierce, Emily; Herr, Megan; et al.
Abstract: A phase 1 study with carfilzomib and vorinostat was conducted in 20 B-cell lymphoma patients. Vorinostat was given orally twice daily on days 1, 2, 3, 8, 9, 10, 15, 16, and 17 followed by carfilzomib (given as a 30-min infusion) on days 1, 2, 8, 9, 15, and 16. A treatment cycle was 28 days. Dose escalation initially followed a standard 3 + 3 design, but adapted a more conservative accrual rule following dose de-escalation. The maximum tolerated dose was 20 mg/m 2 carfilzomib and 100 mg vorinostat (twice daily). The dose-limiting toxicities were grade 3 pneumonitis, hyponatremia, and febrile neutropenia. One patient had a partial response and two patients had stable disease. Correlative studies showed a decrease in NF-κB activation and an increase in Bim levels in some patients, but these changes did not correlate with clinical response.